EVALUATION OF THE STATE DEFENSE PROGRAM IN AN EFFORT TO STRENGTHEN THE SPIRIT OF NATIONALISM IN THE BORDER REGION OF RI - RDTL - Laimeheriwa, Vemy; Komarudin, Komarudin; Triana, Dinny Devi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Border areas have a strategic role in maintaining state sovereignty and national integrity, especially for Indonesia which has direct borders with various countries, one of which is the Democratic Republic of Timor Leste (RDTL). The State Defense Program is one of the government's efforts to strengthen national resilience in the border region by increasing awareness of community nationalism. However, the implementation of this program faces various challenges, such as limited infrastructure, low quality of human resources, and the influence of foreign cultures that can weaken the sense of nationalism of the local community. This study aims to evaluate the effectiveness of the State Defense Program in strengthening the spirit of nationalism in the RI-RDTL border region by using a combination approach of the CIPPO model (Context, Input, Process, Product, Outcome) and the Kirkpatrick evaluation model. Through a qualitative research method with a Narrative Research approach, this study collected data through in-depth interviews, observations, and document analysis from various stakeholders, such as security forces and local communities. The results show that although the State Defense Program has an important role in building nationalism awareness, there are significant obstacles in its implementation, especially related to limited infrastructure and human resources. Therefore, a thorough evaluation and improvement of implementation strategies are needed so that this program can be more effective in strengthening national resilience in the RI-RDTL border region. The results of this research are expected to form the basis of policy recommendations that are more adaptive and sustainable